Efficiency of the application of biological BT preparations in the protection of potatoes from harmful organisms in the western Forest Steppe of Ukraine - Solomiychuk, M.; Pikovskyi , M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2023)
Goal. To study the possibility of using biological preparations of ITI Biotechnca sowing of nightshade crops and to determine their effectiveness against harmful organisms.Methods. Laboratory (identification of pathogens) and field (analysis of vegetation indicators) research methods. The study of the effectiveness of biological preparations was carried out on the basis of the Ukrainian Research Plant Quarantine Station of the Institute of Plant Protection against a natural infectious background. During the growing season, three foliar treatments with drugs were carried out.Results. The research results showed that the use of ITI Biotechnik insecticides provided a better effect on larvae of the Colorado potato beetle of 1—2 ages. The effectiveness of drugs against the Colorado beetle for the drug Bitoxybacillin BT was 71.5%, for Actofit BT — 49.5%, Boverin BT — 80.4%, Metarizin BT — 65.2%. The use of insecticides of biological origin contributed to an increase in vegetation indicators, as well as an increase in the yield of potatoes compared to the control. The use of drugs of a fungicidal and stimulating nature contributed to the growth of yield and higher marketability of potatoes. The highest yield was formed in the Podolyanka variety when treated with BioGibervit BT and was 21.3 t/ha. The best protection against potato diseases was obtained with the use of Bactophyt BT, where the effectiveness against Alternaria was 66.8%, and against late blight — 89.8%. Stimulating drugs provided an immunoprotective effect of 65—70% against phytophthora and 40—47% against Alternaria.Conclusions. The use of a number of individual biopreparations produced by ITI Biotechnika during the growing season makes it possible to control pests, reduce the damage to plants by diseases, and increase the yield of potatoes. Biological drugs and growth stimulants that have shown the best effectiveness can be recommended for the formation of a potato protection system based on BT drugs.